Chronic exposure to environmentally relevant diazepam alters behaviour, gut microbiome, and offspring phenotype in zebrafish (Danio rerio) - Ting Xu; Yilin Huang; Guiling Yang; Wenqin Tu; Ting Luo; Dou Wang; Yuanxiang Jin (Environmental Pollution, 2026)

Identifying the role of Zr4+ cations in enhancing oxygen migration of cerium-zirconium oxides for two-step thermochemical CO2 splitting - Shuaijie Xu; Yanxin Liu; Xi Cao; Guiling Xu; Changsheng Bu (Fuel, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Returning straw and applying appropriate nitrogen fertilizer could increase acid-hydrolysable ammonium nitrogen and amino sugar nitrogen in the soil, thereby promoting effective panicle number and ultimately boosting rice yield - Linya Lu; Zhengli Song; Yang Hu; Liang Luo; Guiling Xu; Yuehua Feng; Muhammad Usama Latif; Somsana Phonenasay; Bingping Cui; Xiangjun Xu; Jianhua Huang; Yanni Wei (Plant and Soil, 2026)

Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

Shaking table test on the seismic response of a multifloored grain warehouse structure considering the soil–structure interaction effect - Zhang Yanan; Xu Qikeng; Huang Yilin; Ding Yonggang; Wang Guiling (Soil Dynamics and Earthquake Engineering, 2025)

Recombinant PD1 liposome loading nintedanib for pulmonary fibrosis therapy in mice - Qian Luo; Ying Xie; Jiarui Xu; Yuxin Ren; Shuyuan Xiong; Hongrui Zhang; Yuling Chen; Haocheng Chen; Jinling Wang; Pengyu Huang; Liyu Sun; Peishan Li; et al. (Chemical Engineering Journal, 2025)

C22-Ceramide Derived from Marine Microalgae Emiliania huxleyi Induces Melanosomal Autophagy via JNK/c-Jun Signaling Pathway in Mouse B16 Melanoma Cells - Jiyue Wan; Hui Ma; Yuxuan Xu; Shumiao Zhang; Jian Li; Guiling Li; Shiying Huang; Xiaotong Ye; Zhengxiao Zhang; Jingwen Liu (Journal of Ocean University of China, 2025)

Error compensation method of GNSS/INS integrated navigation system based on PSO-LSTM - Guiling Zhao; Yuan Wang; Xu Wang (Advances in Space Research, 2025)

Refining water and carbon fluxes modeling in terrestrial ecosystems via plant hydraulics integration - Shanshan Sun; Lingcheng Li; Zong-Liang Yang; Guiling Wang; Nate G. McDowell; Ashley M. Matheny; Jian Wu; Shiqin Xu; Hui Zheng; Miao Yu; Dagang Wang (Agricultural and Forest Meteorology, 2024)

A genome-wide association study and an accurate genotyping strategy to identify and validate the SNPs related to the larval period in bullfrog Aquarana catesbeiana - Yanzhe Wang; Guodong Wang; Lili Zhang; Wencheng Xu; Guiling Zhang; Hui Ge (Aquaculture International, 2024)

Ecological transitions in Xinjiang, China: Unraveling the impact of climate change on vegetation dynamics (1990–2020) - Haichao Hao; Junqiang Yao; Yaning Chen; Jianhua Xu; Zhi Li; Weili Duan; Sadaf Ismail; Guiling Wang (Journal of Geographical Sciences, 2024)

Synthesis of Mn/Cu co-doping mesoporous carbon by template method for gas phase mercury removal - Ruhao Gong; Haihui Chen; Xiuya Rao; Jihong Chi; Ziqi Zhang; Guiling Xu; Dandan Chen; Qiang Zhou; Ping Lu (Fuel, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

Heritability Estimates for Growth Traits and Correlation Analysis between Weight and Metamorphosis Rate in the Bullfrog Rana (Aquarana) catesbeiana - Wencheng Xu; Yanzhe Wang; Guodong Wang; Lili Zhang; Guiling Zhang; Zhipeng Huo; Hui Ge (Fishes, 2024)
Metamorphosis is a crucial process in the life cycle of Rana (Aquarana) catesbeiana. R. catesbeiana tadpoles, in their short larval period, possess a high survival rate and also a highly competitive ability in the amphibious stage. In actual seed production, the economic traits of larval period and metamorphosis rate are used as quantifiable indicators of quality for individuals and populations, respectively. However, studies of these economic traits in larval cultivation and production are still lacking. In this study, we constructed 40 full-sib families of R. catesbeiana and measured the weight and metamorphosis rate of tadpoles at different developmental stages. Subsequently, we calculated the phenotypic and genetic association between weight and metamorphosis rate in tadpoles and assessed the heritability of these two traits. The heritabilities of weight at three developmental stages were all higher than 0.40 and decreased with advancement of the developmental stage; the heritability of the metamorphosis rate was 0.18 ± 0.20, a moderate level. Correlation analysis of weight and metamorphosis rate at each developmental stage in each tadpole family showed that weight at stages 25-I, 25-II, and 25-III was significantly correlated at the phenotypic level but non-significantly at the genetic level. The metamorphosis rate was only moderately associated with stage 25-III weight (0.38, p

Coupled THMC modeling on chemical stimulation in fractured geothermal reservoirs - Haoran Xu; Guihong Liu; Zhihong Zhao; Feng Ma; Guiling Wang; Yuedu Chen (Geothermics, 2024)

Hormesis in the heavy metal accumulator plant Tillandsia ionantha under Cd exposure: Frequency and function of different biomarkers - Jingyi Zhang; Zhen Tang; Evgenios Agathokleous; Guiling Zheng; Liang Xu; Peng Li (Science of The Total Environment, 2023)

Adsorption, regeneration and kinetic of gas phase elemental mercury capture on sulfur incorporated porous carbon synthesized by template method under simulated coal-fired flue gas - Qiang Zhou; Feifei Zhu; Ruhao Gong; Jihong Chi; Jiahong Sun; Guiling Xu; Ping Lu (Fuel, 2023)

Modulation of non-covalent wet adhesion and cohesion via proximally immobilized non-lysine pair structure - Pengxu Wang; Qing Liu; Wenliang Fu; Chao Zhang; Guiling Cai; Weiwei Xing; Hongliang Dai; Hongya Geng; Donggang Xu (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Benthic nitrogen cycling in the deep ocean of the Kuroshio Extension region - Haoming Xu; Guodong Song; Siqi Yang; Ruosi Zhu; Guiling Zhang; Sumei Liu (Frontiers in Marine Science, 2022)
Benthic nitrogen cycling, including nitrification, N-loss, and other nitrogen transformations, plays a crucial role in the marine nitrogen budget. However, studies on benthic nitrogen cycling mainly focus on marginal seas, while attention to the deep ocean, which occupies the largest area of the seafloor, is severely lacking. In this study, we investigate the benthic nitrogen cycling in the Kuroshio Extension region (KE) of the northwest Pacific Ocean at water depths greater than 5,000 m through 15 N enrichment slurry incubation and pore-water dissolved oxygen and inorganic nitrogen profiles. The slurry incubation indicates nitrification is the predominant process in benthic nitrogen cycling. The potential nitrification rates are nearly an order of magnitude higher than dissimilatory nitrate reduction. Nitrification and total N-loss flux estimated from pore-water nitrate and ammonium profiles are 6–42 and 5–30 μmol N m −2 d −1 , respectively. Generally, anammox is the predominant N-loss process in KE sediment. The temperature gradient experiment indicates that the optimum temperature for anammox and denitrification is 13 and 41°C, respectively, partially explaining anammox as the dominant process for deep-ocean benthic N-loss. Both the low concentration of ammonium in pore-water and the discrepant results between anoxic incubation amended with 15 NO 3 − and 15 NH 4 + + 14 NO 3 − suggest that ammonium is another limiting factor for benthic anammox. N-loss activity gradually declines with the distance from the Oyashio–Kuroshio transition zone. However, nitrification has the opposite trend roughly. This reveals that the sediment in KE transfers from nitrate sink to source from north to south. This trend is mainly caused by the variation of primary production and the supplement of active organic matter, which is the energy source for microbes and the potential source for ammonium through remineralization. Overall, our results highlight temperature and ammonium as two limiting factors for deep-ocean benthic N-loss and also exhibit a tight coupling relationship between pelagic primary production and the benthic nitrogen cycle in KE.

Coupled Thermo-Hydro-Mechanical Modeling on the Rongcheng Geothermal Field, China - Feng Ma; Guihong Liu; Zhihong Zhao; Haoran Xu; Guiling Wang (Rock Mechanics and Rock Engineering, 2022)

Sensitivity of Typhoon Lingling (2019) simulations to horizontal mixing length and planetary boundary layer parameterizations - Siqi Chen; Feng Xu; Yu Zhang; Guiling Ye; Jianjun Xu; Chunlei Liu (Frontiers of Earth Science, 2022)

Using triple oxygen isotopes and oxygen-argon ratio to quantify ecosystem production in the mixed layer of northern South China Sea slope region - Zhuoyi Zhu; Jun Wang; Guiling Zhang; Sumei Liu; Shan Zheng; Xiaoxia Sun; Dongfeng Xu; Meng Zhou (Acta Oceanologica Sinica, 2021)

Impact of histaminergic H3 receptor antagonist on hypoglossal nucleus in chronic intermittent hypoxia conditions - Liang Xie; Qinhan Wu; Weiping Hu; Xu Wu; Guiling Xiang; Shengyu Hao; Han Guo; Shanqun Li (Psychopharmacology, 2021)

Toxicological interactions of cadmium and four pesticides on early life stage of rare minnow (Gobiocypris rarus) - Yanhua Wang; Xinfang Li; Chao Xu; Guiling Yang; Dou Wang; Xinquan Wang; Qiang Wang (Ecotoxicology, 2020)

Individual and mixture effects of five agricultural pesticides on zebrafish (Danio rerio) larvae - Yanhua Wang; Guiling Yang; Dejiang Dai; Zhenlan Xu; Leiming Cai; Qiang Wang; Yijun Yu (Environmental Science and Pollution Research, 2017)

HO-1 Signaling Activation by Pterostilbene Treatment Attenuates Mitochondrial Oxidative Damage Induced by Cerebral Ischemia Reperfusion Injury - Yang Yang; Jiayi Wang; Yue Li; Chongxi Fan; Shuai Jiang; Lei Zhao; Shouyin Di; Zhenlong Xin; Bodong Wang; Guiling Wu; Xia Li; Zhiqing Li; et al. (Molecular Neurobiology, 2016)

Polycyclic aromatic hydrocarbons in urban soils of Hangzhou: status, distribution, sources, and potential risk - Guoguang Yu; Zhiheng Zhang; Guiling Yang; Weiran Zheng; Lihong Xu; Zheng Cai (Environmental Monitoring and Assessment, 2014)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)